Implementation of Watermelon Juice Therapy in Reducing Blood Pressure Among Hypertensive Patients Based on Virginia Henderson’s Nursing Theory at UPTD Tresna Werdha Social Institution Bengkulu - Hartti, Nisy Dwi; Metasari , Des (Utami Publisher, 2026)
Hypertension is one of the most common non-communicable diseases in the elderly and is a major risk factor for cardiovascular disease. Non-pharmacological interventions such as watermelon juice therapy, which contains L-citrulline, potassium, and antioxidants, are believed to help naturally reduce blood pressure.This study aims to evaluate the effectiveness of watermelon juice administration in reducing blood pressure among elderly individuals with hypertension using the Virginia Henderson nursing theory approach.The method used in this study was a descriptive design with a case study approach involving two elderly patients at the UPTD Tresna Werdha Social Institution Bengkulu. Data were collected through observation, interviews, and blood pressure measurements before and after the intervention. Nursing interventions were provided based on Virginia Henderson’s 14 fundamental needs.Watermelon juice therapy can be used as a complementary intervention in the management of hypertension in the elderly. The application of Virginia Henderson’s nursing theory supports successful adaptation and lifestyle modification in individuals with hypertension.